DFT Study of CO2 Adsorption and Hydrogenation on the In2O3 Surface - Ye, Jingyun; Liu, Changjun; Ge, Qingfeng (Journal of physical chemistry. C, 2012)
Catalytic conversion of CO2 to liquid fuels or valuable chemicals is an attractive alternative to geological sequestration. In the present study, we applied density functional theory slab calculations in the investigation of the adsorption and hydrogenation of CO2 on the (110) surface of In2O3. Our results indicate that the adsorbed CO2 is activated, forming a surface carbonate species by combining with surface oxygen, and has an adsorption energy of −1.25 eV. Heterolytic dissociative adsorption of H2 results in a surface hydroxyl from H binding the surface O site and a hydride from H binding the In site. The migration of H from the In site to the neighboring O site is energetically favorable but has a significant activation barrier of 1.32 eV. Water may adsorb on the surface either molecularly or dissociatively, with adsorption energy of −0.83 eV and −1.19 eV, respectively. Starting from CO2 coadsorbed with the H adatoms on the In2O3 surface, we examined two possible conversion pathways for CO2: (a) CO2 is hydrogenated by the H adatom on the In site to form a surface formate species (HCOO); (b) CO2 is protonated by the H adatom on the O site to form a surface bicarbonate species (COOH). Reaction a is endothermic by +0.33 eV, whereas b is exothermic by −0.78 eV. Although the formation of the bicarbonate species is energetically favorable, the subsequent step to form CO and OH is highly endothermic, with a reaction energy of +1.07 eV. Furthermore, the bicarbonate species can react with a surface hydroxyl easily, resulting in coadsorbed H2O and CO2. These results indicate that hydrogenation of CO2 to the formate species is favorable over protonation to the bicarbonate species on the In2O3 surface. These results are consistent with the experimental observations that the indium oxide based catalyst has a high CO2 selectivity and H2O resistance.